The effect of high environmental temperature on growth performance of Japanese quails with different body weights - Ozbey, O.; Ozcelik, M. (Asian Network for Scientific Information, 2004)
In this study, it was aimed to determine the effect of high environmental temperature on live weight, feed consumption, feed efficiency, survivality and some carcass features of Japanese quails with different body weights. During such research, total 550 quail chicks were used in addition, two different temperature groups as being the control (18-24°C) and experiment (35°C) groups and two different body weight groups consisting of heavy (live weight > 27 g) and light (live weight < 27 g) groups were identified. As the result of the research, the live weight, feed consumption, feed efficiency and survivality were found less at 35°C compared with 18-24°C in both heavy and light weight groups. Such decrease was noted as more efficiently in heavy group. © Asian Network for Scientific Information, 2004.
Keywords: Body weight; Environmental temperature; Japanese quail